Antioxidative, Anti-Inflammatory, and Anticancer Effects of Purified Flavonol Glycosides and Aglycones in Green Tea - Chan-Su Rha; Hyun Woo Jeong; Saitbyul Park; Siyoung Lee; Young Sung Jung; Dae-Ok Kim (MDPI AG, 2019)
(1) Background: Extensive research has focused on flavan-3-ols, but information about the bioactivities of green tea flavonols is limited. (2) Methods: In this study, we investigated the antioxidative, anti-inflammatory, and anticancer effects of flavonol glycosides and aglycones from green tea using in vitro cell models. The fractions rich in flavonol glycoside (FLG) and flavonol aglycone (FLA) were obtained from green tea extract after treatment with tannase and cellulase, respectively. (3) Results: FLG and FLA contained 16 and 13 derivatives, respectively, including apigenin, kaempferol, myricetin, and quercetin, determined by mass spectrometry. FLA exhibited higher radical-scavenging activity than that of FLG. FLG and FLA attenuated the levels of intracellular oxidative stress in neuron-like PC-12 cells. The treatment of RAW 264.7 murine macrophages with FLG and FLA significantly reduced the mRNA expression of inflammation-related genes in a dose-dependent manner. Furthermore, FLG and FLA treatments decreased the viability of the colon adenoma cell line DLD-1 and breast cancer cell line E0771. Moreover, the treatment with FLG or FLA combined with paclitaxel had synergistic anticancer effects on the DLD-1 cell line. (4) Conclusions: Flavonols from green tea exerted beneficial effects on health and may be superior to flavan-3-ols.